A fluorescent sensor for highly selective sensing of nitro explosives and Hg(ii) ions based on a 3D porous layer metal–organic framework. Issue 25 (24th May 2016) - Yang, Liu; Li, Xiao; Qin, Chao; Shao, Kui-Zhan; Su, Zhong-Min
Abstract : A 3D porous layer metal–organic framework, [Cd(BPDC)0.5 (L1)(NO3 )]·3.4DMF (1 ), was successfully synthesized under solvothermal conditions. The stability of the framework, small molecule sensing, explosives detection and Hg(ii ) ion sensing properties were investigated. Abstract : A 3D porous layer metal–organic framework, namely [Cd(BPDC)0.5 (L1)(NO3 )]·3.4DMF (1 ), was synthesized under solvothermal conditions. The structure was characterized by single crystal X-ray diffraction analysis, powder X-ray diffraction (PXRD) analysis, thermogravimetric analysis (TGA), infrared spectrophotometry analysis and elemental analysis. The structure of1 displays a 3D porous layer and can be classified as a (3, 4)-connected topology with a point symbol of (4 2 ·6·3 8 )2 (4 2 ·6). The framework is stable to a certain degree.1 can also be applied as a fluorescent sensor for small-molecule sensing, such as nitrobenzene (NB) and 2, 4, 6-trinitrophenol (TNP). In addition, 1 is a rare example of MOF-based fluorescent probes targeting environmentally relevant guest species, such as Hg(ii ) ions in aqueous solution, with high selectivity and sensitivity.